CTX-M-127 with I176F mutations found in bacteria isolates from Bangladeshi circulating banknotes - Md. Zannat Ali; Sankaranarayanan Srinivasan; Selina Akter (Scientific Reports, 2024)
Abstract Extended-spectrum beta-lactamase (ESBL)-producing organisms are widely recognized as clinically relevant causes of difficult-to-treat infections. CTX-M has formed a rapidly growing family distributed worldwide among a wide range of clinical bacteria, particularly members of Enterobacteriaceae. Circulating banknotes, exchanged daily among people, pose a potential vehicle for transmitting multidrug resistance. We screened for ESBL-carrying bacteria in the present study and reported CTX-M mutations in Bangladesh's banknotes. We sequenced the genes and performed homology modeling using the Swiss model with CTX-M-15 (4HBT) as a template. Then, we performed molecular docking of mecillinam with the template and the generated model using Autodock 4.2 (Release 4.2.6). After docking, we visually inspected the complexes built using Autodock tools for polar contacts and pi-pi interactions in PyMOL 2.5.4. Our partially sequenced bla CTX-M was related to bla CTX-M-10 and bla CTX-M-15. We observed multiple single-nucleotide substitution mutations, i.e., G613T (silent mutation), A626T (I176F), and A503G (N135D). Homology modeling showed high similarity when the model was superimposed over the template. The orientation of Asn (135) in the template and Asp (135) in the model does not show a significant difference. Likewise, Ile (176) in the template and Phe (176) in the model offer the same orientation. Our generated model could bind to Lys237, Ser240, and Asp135 residues with the lowest binding energy on docking. Our predicted binding of the mecillinam to the mutated D-135 residue in the model indicates contributions and supports previous reports proposing CTX-M-15 to CTX-M-127 mutational conversion on the mecillinum resistance phenotype.